منهج الإمام النقاش في تفسيره شفاء الصدور: دراسة تحليلية لسور ‏الفاتحة والزهراوين والنساء - مهيري، حمدة بنت خليفة بن سيف (Kulliyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2018)
Al-Naqqash was a great Muslim scholar of tafsir, hadith, fiqh, linguistics, Arabic philology, and Arabic poetry during the period covering 3rd and 4th centuries. This thesis focuses mainly on his methodology of Qur'anic interpretation as applied by him in his work “Shifa al-Sudur”, with special reference to the interpretation of the first four Surahs in the Qur'an- al-Fatihah, al-Baqarah, Ali Imran, and al-Nisa'. The issues discussed at length in the thesis include political, economic, and religious situations during the time of al-Naqqash, which seem to have influenced al-Naqqash's approach in his writings especially his Tafsir work. As for his methodology of tafsir, as critically analysed in the thesis, he uses several sources for that: the Qur'an, the Hadith, the views of the Companions and the Successors, the Judeo-Christian traditions, his own independent reasoning, Arabic syntax and philology, and classical Arabic poetry. His rational approach chiefly based on linguistic principles of Arabic in the Qur'anic interpretation makes him quite distinct from others in the field of tafsir. It is this very reason that his tafsir work is considered a very significant contribution in the linguistic interpretations of the Qur'an. The methodology applied in the thesis is triangular, inductive, analytical and comparative. The conclusion reached at in the thesis is that the tafsir work of al-Naqqash is of immense value as it represents all the four trends in tafsir: traditional, rational, jurisprudential, and linguistic.